The Substantive Justice Indonesia Bancrupty Law - Heryanty Hasan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Law Number 37 of 2004 was designed to balance creditors’ rights with debtor rehabilitation in insolvency processes in the fair resolution of bankruptcy disputes. This normative legal research uses statutory and conceptual approaches that apply. This study identifies judicial mechanisms in the commercial court regarding the criteria for breach of contract when insolvency occurs, which may allow abuse through bankruptcy filings by debtors carried out by creditors to pursue additional objectives, which can result in the liquidation of companies.